CATALYZING RELIGIOUS MODERATION AND GENDER EQUALITY USING DIGITAL ISLAMIC COUNSELING GUIDANCE IN WEST JAVA ISLAMIC BOARDING SCHOOL - Kusnawan, Aep; Rustandi, Ridwan; Gumilar, Setia; Ali, Muhamad (State Islamic University (UIN) of Sunan Ampel Surabaya, 2025)
This study examines the implementation of counselling guidance to strengthen religious moderation and gender equality through digital counselling guidance in modern Islamic boarding schools in West Java. Using a qualitative-interpretive approach, this study involved Islamic boarding schools in seven districts/cities, focusing on female students aged 15-25. The results of the survey reveal the development of a digital counselling guidance framework that integrates Islamic moderation values and counter-narrative strategies for gender-based cyber violence. This framework includes four dimensions: digital connection skills, content access, contextual understanding, and interaction in digital space, referring to UNESCO and Kemenkominfo standards. The implementation of digital counselling guidance is carried out through the stages of instilling, coaching, mentoring, and competency development, and it is applied at the individual, interpersonal, and institutional levels. This process follows the connect-content-context-contact cycle, emphasizing the importance of building constructive and inclusive media literacy awareness. This study significantly empowers Islamic boarding school communities to face digital challenges, promoting moderate Islam and gender equality in the digital era.